2013
DOI: 10.1039/c2cc37157j
|View full text |Cite
|
Sign up to set email alerts
|

Controlled folding of a novel electroactive polyolefin via multiple sequential orthogonal intra-chain interactions

Abstract: We report here the synthesis of a novel electroactive polyolefin and demonstrate through a combination of SEC-MALS and DLS how this type of functional polymer can be folded in a controlled fashion from an expanded coil to a tightly wound globule using sequentially activated noncovalent and covalent intra-chain interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 24 publications
3
78
0
Order By: Relevance
“…A third method for SCNP fabrication takes advantage of multiple orthogonal chemistries triggered sequentially to fold synthetic chains into particles [31]. Scheme 3 shows a series of poly(oxanorbornene anhydride-co-cyclooctadiene) materials synthesized using ROMP.…”
Section: Polymer Design and Scnp Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A third method for SCNP fabrication takes advantage of multiple orthogonal chemistries triggered sequentially to fold synthetic chains into particles [31]. Scheme 3 shows a series of poly(oxanorbornene anhydride-co-cyclooctadiene) materials synthesized using ROMP.…”
Section: Polymer Design and Scnp Synthesismentioning
confidence: 99%
“…This sequential folding approach demonstrates that the application of orthogonal chemistries in a synergistic fashion results in more tightly collapsed structures with the goal of more closely mimicking natural folded polymeric constructs. [31] SCNP characterization Conventional SEC SEC with conventional calibration is the standard method used to characterize SCNPs formation. Comparing the retention time of the parent polymer chains to the retention time of the folded nanoparticles after intramolecular crosslinking is induced typically reveals shifts to longer retention times.…”
Section: Polymer Design and Scnp Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…26 Actual M w values for SCNPs N1-5 as determined from static light scattering (SLS) data were consistent to those of the corresponding P1-5 precursors (see Table 2). 27,28 Complementary dynamic light scattering (DLS), transmission electron microscopy (TEM) and atomic force microscopy (AFM) measurements provided evidence of individual SCNP formation. A reasonable agreement was found between data from different techniques (probably due to the presence of residual solvent in the samples during TEM and AFM measurements).…”
mentioning
confidence: 99%
“…Though advanced methods have been recently introduced to produce compact SCNPs in good solvent 19,20 , the latter are more the exception than the rule. Recent works by small-angle neutron and X-ray scattering (SANS and SAXS) have indeed revealed that, in general, SCNPs in good solvent and high dilution are open sparse objects 7,11,21,22 .…”
Section: Introductionmentioning
confidence: 99%